Analysis of the Effect of Capital Expenditure and Labor on Economic Growth in the Pohuwato District - Muh Fiqra Wardi (Manunggal Halim Jaya, 2021)
Pohuwato Regency is an integral part of Gorontalo Province. Much progress and improvement have occurred beyond that of Boalemo Regency as its parent regency, both in terms of public services and the implications for the regional economy. Especially in the Capital Expenditure budget item which continues to increase and the absorption of the workforce is increasingly higher. In the long term (8 years) fluctuating movements in Capital Expenditure can normally be followed by a graph of Economic Growth. On the other hand, other factors such as labor whose graph continues to climb should be able to increase economic growth by several figures. From these problems, an in-depth study of Capital Expenditures and Labor and the extent of their influence on the Economic Growth of Pohuwato Regency is needed. This study aims to determine whether Capital and Labor Expenditures affect the Economic Growth of Pohuwato Regency. This study uses multiple linear regression analysis. The source used in this research is secondary data. Secondary data in this study used time series data for 2007-2014. The result is that the Capital Expenditure and Manpower variables partially and simultaneously have a positive and significant effect on the Economic Growth of Pohuwato Regency from 2007-2014. Among the independent variables, the variable Manpower has the most dominant influence on the Economic Growth of Pohuwato Regency.